ZAKAT AND ECONOMIC DEVELOPMENT: STUDY IN THREE MUSLIM COUNTRIES IN SOUTHEAST ASIA - An’im Kafabih; Setyo Tri Wahyudi (Universitas Negeri Medan, 2020)
The objective of this study is to analyze the effect of zakat on per capita income as one indicator of economic development. The data is analyzed by Cobb-Douglas production function and panel data analysis model. Study findings show that zakat significantly and positively affect on per capita income. This study also found that compared to Foreign Direct Investment (FDI), most popular instrument of government to increase economic development, zakat has a greater coefficient. In addition, Muslims as a majority population on average unable to contribute significantly to economic development. However, they could contribute to zakat as seen from increase in amount of zakat collection.